War and Cold War in American Foreign Policy, 1942-62
XXII, 250 p.
Keywords: Making use of newly-researched archival material, this collection of original essays on wartime and postwar US foreign policy re-evaluates well-known crises and documents many less familiar aspects of the nation's mid-twentieth century conflicts. Leading diplomatic historians address familiar subjects from new angles. They offer new evidence about the risks run and the costs incurred in the prosecution of the Cold War, from Korea to the Caribbean. And they provide up-to-date accounting of mid-twentieth century American diplomacy's global purposes and consequences.